2019
DOI: 10.3390/molecules24040668
|View full text |Cite
|
Sign up to set email alerts
|

Study on Speciation of As, Cr, and Sb in Bottled Flavored Drinking Water Samples Using Advanced Analytical Techniques IEC/SEC-HPLC/ICP-DRC-MS and ESI-MS/MS

Abstract: The main aim of the research was to develop a complementary analytical approach consisting of bespoke speciation analysis and non-targeted speciation analysis of As, Sb, and Cr in flavored bottled drinking water samples using HPLC/ICP-DRC-MS and ESI-MS/MS. The scope of two previously developed analytical procedures, (1) multielemental speciation procedure for AsIII, AsV, CrVI, SbIII, and SbV analysis and (2) arsenic speciation procedure for AsB, AsIII, DMA, MMA, and AsV quantification, was extended to the anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 46 publications
1
15
0
Order By: Relevance
“…We applied the method previously developed in our laboratory for the speciation analysis of five toxic species of As, Cr, and Sb in drinking water samples using IEC/ICP-DRC-MS comprising two speciation procedures [32]. The procedures were extended to ensure that it would apply to flavored and functional bottled drinking waters.…”
Section: Determination Of Inorganic Species Of As Cr and Sbmentioning
confidence: 99%
See 2 more Smart Citations
“…We applied the method previously developed in our laboratory for the speciation analysis of five toxic species of As, Cr, and Sb in drinking water samples using IEC/ICP-DRC-MS comprising two speciation procedures [32]. The procedures were extended to ensure that it would apply to flavored and functional bottled drinking waters.…”
Section: Determination Of Inorganic Species Of As Cr and Sbmentioning
confidence: 99%
“…The speciation analysis of organic species of As, Cr, and Sb was conducted only in cases when mass balance analysis showed significant differences between amounts of TAs, TCr, and TSb and concentrations of known As, Cr, and Sb species. Screening of metal complexes in water samples using SEC/ICP-DRC-MS was conducted, followed by an identification of possible complexes with the use of ESI-MS/MS [32].…”
Section: Determination Of Organic Species Of As Cr and Sbmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the introduction of ICP-MS equipped with collision/reaction cell (CRC) or dynamic reaction cell (DRC) is an effective approach to overcome these problems linked with polyatomic interferences, among which the DRC technique is introduced by using the reacting gas, such as ammonia, hydrogen, oxygen, etc. The reacting gas overcomes these interferences by atom transfer or charge transfer reactions to break the polyatomic ions into atoms or ions with different m / z [121,177,178]. For example, a DRC for spectral interferences elimination by using oxygen and ammonia as reaction gases was developed by Marcinkowska et al [178] for multielemental speciation analysis of Cr(VI), As(III) and As(V) in water by advanced hyphenated technique HPLC/ICP-DRC-MS.…”
Section: Detection Techniques For Speciation Analysismentioning
confidence: 99%
“…Flavoured bottled water (FW), carbonated (sparkling) and still, are gaining popularity among consumers in recent years (Lorenc et al, 2019;Bilek et al, 2014;Brown et al, 2007). It was reported that retail sales of FW have increased by 72% in 2018 (Purdy, 2019).…”
Section: Introductionmentioning
confidence: 99%